α-Fluorination of Nitrobenzenes and Nitropyridines via Vicarious Nucleophilic Substitution of Hydrogen - Al-Mkhaizim, Fayez Y.; Greaney, Michael F. (Synlett, 2020)
A highly selective C–H functionalization of nitrobenzenes and nitropyridines is reported using tandem vicarious nucleophilic substitution (VNS) chemistry with electrophilic fluorination using Selectfluor®. The process generates tertiary benzylic fluorides in good yield under simple, mild conditions and short reaction times.
Keywords: fluorination; vicarious nucleophilic substitution; C–H functionalization